Begonia depressinerva (sect. Baryandra, Begoniaceae), a new species from Luzon Island, the Philippines - Pranada, Mc Andrew K.; Luna, Christine Joy S.; Mendez, Noe P.; Calapatia-Salvador, Ma. Eleanor (Phytotaxa, 2019)
A new peltate species of Begonia sect. Baryandra from Kidadayaig Falls, General Nakar, Quezon is described and illustrated here. The new species, B. depressinerva, is diagnosed against the morphologically similar B. tayabensis. The two species are similar by having rhizomatous stem, peltate, ovate leaf, and 5-tepalled pistillate flower, but the new species is remarkably different by having densely pilose, asymmetric leaf blade, densely pilose petiole that is inserted much closer to the basal margin, obtuse to subobtuse staminate flower outer tepal apex, and glandularly hairy ovary. B. depressinerva is proposed to be Vulnerable (VU) D1, following the guidelines of the IUCN.